A systematic review of the relationship between social and emotional competencies and student engagement in youth - Santos, A. C.; Simões, C.; Melo, M. H. S.; Santos, M.; Freitas, I.; Branquinho, C.; Cefai, C.; Arriaga, P. (Educational Research Review, 2023)
Student engagement (SE) is known as one of the most relevant predictors of academic achievement and completion. Social and emotional competencies (SECs) are well established as critical skills for healthy and adaptative youth development. This systematic review investigated the associations between SE and SECs in 10 to 25 years old students. The review followed PRISMA guidelines. Nine databases were searched for peer-reviewed literature published between 2004-2020. A total of 91 studies were selected, including 92879 youth students. Emotional engagement is the most studied dimension of student engagement and largely surpasses the number of studies that analysed the multidimensional SE concept. The number of studies in each of the five CASEL domains is uneven, with more studies focussing on self-management, self-awareness, and relationship skills, in association with SE. Overall, most studies showed that SECs are positively associated with SE and negatively associated with disengagement, with similar results for middle, high school and university students from different backgrounds, suggesting that educational institutions should implement social and emotional learning programmes to increase SE. Studies that reported age and gender differences regarding SE showed unanimously higher SE values for girls and younger students. There is a clear need for studies using the multidimensional SE concept, including university students, and applying cross-cultural analyses.